COLLECTIVE ZAKAH INITIATIVES IN KERALA - Rosina Padayanvalappil; Dr. C P Shaheed Ramzan (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
Abstract: This article examines the evolution of Zakah management in Kerala, India, within a secular context. It traces historical developments, highlighting the transition from individualized charity to organized Zakat systems. Through survey findings, it explores contemporary practices and challenges, emphasizing the need for improved collection and disbursement strategies. Despite diverse approaches to Zakat calculation and distribution, there is a prevalent satisfaction with Zakat committees' performance. The article underscores Zakat's potential beyond the Muslim population, noting its impact on socio-economic welfare. It advocates for collective, structured Zakah systems to enhance efficiency and maximize the impact of Zakat in addressing socio-economic challenges and promoting community welfare in Kerala.